Analisa Penerapan Warehouse Management System terhadap Pelayanan Suplai Komponen Menggunakan Six Sigma - Basuki . (JURNAL CITRA WIDYA EDUKASI, 2018)
This research was conducted in the logistics department of PT XYZ, which is an automotive manufacturing company that produces four-wheeled vehicles and two-wheeled vehicles. About 1,000 component items are needed to produce a four-wheeled vehicle. If one of them is shortage or not available, then the production unit will not pass the test, so that the completeness of the component becomes an important point. The logistic department will guarantee the availability of these components. Ideally, components may not be late, but actually, there is still a shortage of components, so the production unit must wait for the availability of these components. The management of PT XYZ sees this condition must be immediately overcome by implementing a Warehouse Management System (WMS). The research was conducted by analyzing the implementation of WMS to determine it effectiveness. The object of this research is that child parts are ordered in parts (part by part). The analysis carried out is measuring the shortage of components before and after the implementation of WMS by using six sigma (6-Sigma). The result shows that the sigma level before implementation is 3.07-Sigma and after 6 months of implementation, the sigma level becomes 3.97-Sigma. This shows that the implementation of WMS is quite effective to reduce the possibility of component shortages.